Palisade technique as an effective endoscopic submucosal dissection tool for large colorectal tumors - Suzuki, Yuichiro; Ohata, Ken; Sakai, Eiji; Negishi, Ryoju; Takita, Maiko; Minato, Yohei; Muramoto, Takeshi; Chiba, Hideyuki; Tsuji, Yosuke; Matsuhashi, Nobuyuki (Endoscopy International Open, 2021)
Background and study aims Endoscopic submucosal dissection (ESD) has become the standard treatment for colorectal ESD, but large colorectal tumors remain difficult to remove. We developed a new method, called the palisade technique, by modifying the multiple tunneling technique. In this method, a palisade of submucosal tissue is left beneath the tumor to anchor a dissected specimen, maintaining effective submucosal traction.Patients and methods The study included 11 patients with large colorectal tumors that were over half the circumference of the colorectal lumen which were treated using the palisade technique from August 2017 to October 2019. Overall resection outcomes were assessed.Results All 11 lesions were removed en bloc. The R0 resection rate was 45.6 % because of marginal burning of the specimen, but no local recurrence was found after a median observation period of 31 months. The median submucosal dissection time (SDT) and submucosal dissection speed (SDS) were 170 minutes and 23.1 mm2/min, respectively. One case of post-ESD hemorrhage was successfully managed endoscopically, and two cases of post-colorectal ESD coagulation syndrome were managed conservatively.Conclusion The palisade technique can be an effective and safe technique for treating large colorectal tumors that extend over half the luminal circumference.